Vanishing Returns? Potential Returns and Constraints to Input Adoption among Smallholder Farmers in Uganda - Hill, Ruth; Mejia-Mantilla, Carolina; Vasilaky, Kathryn (World Bank, Washington, DC, 2018)
This paper estimates the profitability of fertilizer and hybrid seeds in Uganda, using agronomic evidence on the yield returns to inputs from experimental fields, as well as output price data from local markets between 2000 and 2012. The results suggest that the returns to fertilizer are positive across the entire price range for beans, maize, and matooke and positive for the top 75 percent of prices for coffee. Commonly available improved seed varieties for maize and beans increase gains by 32 percent on average. However, accounting for the quality of the inputs available to farmers in the market, the sizable positive returns become negative for most of the price distribution, possibly explaining the low adoption of inputs in Uganda. The paper also examines the impact of other factors that could affect input adoption, by using a relatively long panel data set spanning 12 years. The analysis finds evidence that enhanced access to economic markets and past weather conditions have small effects on input use, and positive correlations between the use of extension services and knowledge and input use.